The individual and associated use of monensin, tannins and calcium nitrate in the feeding of cattle promote a reduction in the emission of methane gas - Assumpção, Alice Helena Peres Marques (2021)
The aimed of this study was to evaluate the individually and combine use of monensin, tannins of Acacia mearnsii extract and calcium nitrate on ruminal fermentation parameters (ex-situ technique), rumen microbiome as well as on anaerobic biodigestion of waste. The dissertation was structured in two studies. In study 1, five cannulated Nellore cows, non-pregnant and non-lactating, with a mean body weight of 530±75 kg, were distributed into a 5 x 5 Latin square. The animals were fed with a basal diet, concentrate:roughage (corn silage) ratio of 60:40, through which the additives were supplied totaling five treatments: control (without addition of additives), monensin (300 mg in the diet), tannin (1.5% of DM), nitrate (3.0% of DM), and Pool (combination of the doses of the three additives). Data were analyzed using PROC MIXED of SAS and differences were declared significant at 5%. Cows fed with tannins had an increase of 23% on dry matter and gross energy intake. A reduced CH4 production was observed when the control treatment was compared to the individual or combined use of all additives, being 9.5% related to monensin treatment, 18.75% in tannin, 19.8% in calcium nitrate and a reduction of 28.8% when cows were fed with the pool (monensin, nitrate and tannin). Regarding the ruminal microbiota, no effects were found on the total protozoan count when cows were fed with the pool in comparison to the control. Furthermore, the structure of members using PCoA of the bacterial community of the rumen of cows fed with the pool had differences when compared to cows fed with monensin and tannin, but the bacterial community observed in the pool group was similar to those of cows fed with nitrate. Overall, significant decreases in rumen methane emissions can be achieved without drastic effects on either the rumen microbial population or its function. In study 2, biodigesters were arranged in a completely randomized design of 5 treatments with 5 replicates, totaling 25 experimental units (feces were the main variable from cows fed with the individual or combined use of all additives). The data were analyzed by using the Statistical Analysis System (SAS 9.3, Institute Inc., 2013). The biodigesters supplied with waste from cattle fed tannins increased in 91% of CH4 production and 52% of CO2 production per gram of volatile solids. The pool treatment increased the biofertilizer nutrient compounds in 12.6% of Total C and 35% of Total N, monensin presented an increase of 7.5% of Total N, and K was increased in 35% to tannins and 22% to nitrate. The monensin did not present the potential for CH4 production in relation to the waste in the environment. Interestingly, the tannins showed significant results through anaerobic digestion, being its use recommended with the attempt to reduce the impacts of untreated manure on the environment. More studies are necessary to understand how nitrate acts on biodigesters.